Comprehensive review of wire arc additive manufacturing: Hardware system, physical process, monitoring, property characterization, application and future prospects - Li, Yan; Su, Chen; Zhu, Jianjun (Results in engineering, 2022)
Wire arc additive manufacturing (WAAM) outstandingly features in lower cost and higher efficiency than other metal additive manufacturing technologies, which has a great potential in large-scale industrial production. The paper gives a detailed review, which involves WAAM hardware system, physical process, monitoring, property characterization, application and future prospects, to facilitate quick and easy understanding of current status and future prospects of WAAM. WAAM hardware systems are of primary importance and mainly based on four types of arc welding machine. The paper summarized the features of different hardware systems, displayed their suitability for different raw materials, and discussed their respective advantages. There is complex physical phenomenon in WAAM, and many technological parameters, such as heat input, current, wire feeding speed and so on, are investigated to understand the physical mechanism. Monitoring is essential for the additive process, in which optical inspection, spectral sensing, acoustic sensing, thermal sensing, electrical sensing and multi-sensor monitoring system all have been applied. Property characterization is always done to evaluate the quality of additive parts, and typical defects such as high residual stress, deformation, porosity, crack and delamination are reported. Examples of industrial products fabricated by WAAM are introduced. Finally, the paper concluded six possible research directions in future. It is necessary to establish detailed databases about additive parts for sorted hardware systems and metals with suitable operating conditions. Hybrid additive and subtractive technology, additional rolling or temperature control process, multi-scale and multi-physics research, multi-variable monitoring system, and artificial intelligence would help to improve the manufacturing level. •Provide a comprehensive review of WAAM according to manufacturing procedure.•Summarize their own features of various WAAM systems.•Help to choose the most suitable WAAM hardware system.•Multi-scale and multi-physics research on WAAM is recommended.